Emerging Patterns of HRM: The Influence of Social Ties and 'Guanxi' on Recruitment and Selection in China - WONG, YU HONG (2008)
This is an investigation of guanxi and social ties that may influence the recruitment and selection and also the Human Resource Management (HRM) practices in the Chinese business environment. The purpose of this research is to examine how guanxi and social ties influence hiring practices in different business ownerships and which HRM model is the most suitable for China. Interviews and three case studies were conducted to examine this research question. Results indicate that ÃÂ¢Ã¢ÂÂ¬ÃÂguanxi" and social ties can influence recruitment and selection decisions and they are still a common method for hiring in China. A hybrid model which combines both Chinese and Western HRM practices should be used. However, results also found that guanxi and social ties might be less important in the future.